Differential evolution particle swarm optimization algorithm for reduction of network loss and voltage instability - Vaisakh, K.; Sridhar, M.; Linga Murthy, K.S. (2009 World Congress on Nature and Biologically Inspired Computing, 2009)
This paper introduces a differential evolution particle swarm optimization (DEPSO) method for dealing with optimal reactive power dispatch aiming at power loss reduction and voltage stability improvement. The optimum reactive power dispatch of power systems is to allocate reactive power control variables so that the objective function composed of power losses is minimized and the prescribed voltage limits are satisfied. The proposed method determines the optimum settings of reactive power control variables such as, generator excitation, tap changing transformers, and shunt compensation that reduces the power loss, while maintaining the voltage stability. IEEE-30 bus test system from the literature is used to exemplify the performance of the proposed method. Numerical results show that the proposed method is better than the other methods reported in the literature.